Contribution à l’histoire de la boulangerie romaine : étude de « pains/galettes » découverts en Gaule - Andreas G. Heiss; Véronique Matterne; Nicolas Monteix; Margaux Tillier; Camille Noûs (Gallia)
Over the past several decades, both the philosophy of cultural, social and historical anthropology have focused on the many avenues of study relating to food, or rather modes of consumption, by focusing on the construction of individual and collective identities. As a counterpoint to these theoretical considerations, archaeological experience brings its share of concrete, though uncertain observations, discoveries, and interpretations that arise from both the artefacts and their related contexts. While raw foodstuffs –ecofacts– are regularly found and identified in archaeological contexts in the form of seeds and fruits, observations on food preparations are rarer, with less attention paid to their analysis and interpretation. These findings pose particular challenges to researchers, as they require an adequate analytical strategy for their study. Many fragments of so-called amorphous charred objects (ACO) can indeed be identified as being processed plant products. On the other hand, items that appear more complete, and whose outer form appears to be the result of intentional shaping, are often “blindly” described as breads or flatbreads. Still, these also require sophisticated technical equipment and extra care in interpretation, as even the mere hypothesis that such an object is cereal-based must be systematically verified. For this reason, it is preferable to refer to these elements as “bread-like objects” (BLO), rather than identifying them straight away as breads or dough. Examination of the surfaces, with the naked eye or by optical microscopy, in most cases does not reveal any identifiable macroscopic component; it is therefore necessary to use appropriate and non-destructive analytical methods. But why focus on the study of these seemingly rare finds anyway? In historical archaeology, the research into consumption practices is more often than not based solely on textual and epigraphic sources, which often do not reveal the phases of food preparation, or do not necessarily apply to a particular region. In contrast, archaeological remains of food preparations reflect the actual outcomes of the physical transformation of natural ingredients into elaborate dishes. Reconstructing these transformation processes by analysing the micro-structure of food remains therefore opens a new field of research leading to the possibility of reconstituting recipes. In the same vein as the previous considerations, we follow the idea that a dish or a drink represent artefacts, in the current definition as objects “predominantly shaped by human action”. We therefore consider it legitimate to evaluate processed foods, and their archaeological remains, as material witnesses to an ancient culinary heritage and we interpret them as such. This article describes the results of the analysis of six food preparations derived from cereals, discovered in Gaul and dated between the 2nd and the 6th c. CE. It also aims to elaborate on the conceptual environment in which these studies are placed, and the methodological aspects related to them. Considered as processed and shaped artefacts, the BLO can therefore be studied by referring to the concept of the chaîne opératoire (operational sequence). The ingredients, instruments and equipment used, products and by-products generated at each stage of this occasionally complex sequence are used to illustrate and reconstruct the manufacturing process, possibly supported by the experimental reproduction of the actions involved. Based on this concept of the chaîne opératoire, an objective classification of products and by-products can be attempted. Since the primary components of the preparations are no longer identifiable under a binocular magnifying glass, non-invasive imaging techniques are used to facilitate their analysis. Current approaches consist of the search for diagnostic elements to determine the plant foods used. A preliminary scanning electron microscope analysis confirms the presence of dough made from semolina or flour, derived from cereals, but also sometimes from legumes or dried fruits, such as acorns and hazelnuts. Identification of cereals is based, in particular, on tissue fragments from the outer layers of the cereal grain (commonly called “bran” as a whole), or even fragments of glumes or awns, whose micro-anatomy (histology) offer diagnostic characteristics for their identification. Starch granules and yeast spores are also sought after. Chemical approaches using mass spectrometry occasionally supplement these methods, in order to identify certain aspects of their molecular composition. In addition to the attention paid to the basic ingredients, we also endeavour to understand the succession of actions applied to the dough and the way in which they were created and prepared, as well as the cooking methods that they subsequently experienced. Protocols of study are still being refined, in particular for the recognition of fermented doughs, and the criteria that would make it possible to differentiate a bread from a flatbread, for example. Without damaging the archaeological specimen, X-ray microtomography allows for an observation of the internal structure of the dough and the gas bubbles (pores) produced by fermentation, as well as inclusions and additions of ingredients other than flour. Results from initial analysis reveal that the products studied were prepared from extremely pure flours and were very carefully ground and sieved. We note that wheat(s), but also barley are the main components, sometimes mixed, though it is not yet possible to assess the proportions of such mixtures. Examination of the doughs reveals signifcant differences in texture and structure: presence or absence of a crust, pores of varying sizes and frequency, doughs whose air has been kneaded out, etc. The first observations also highlight the high quality of the flour used for making (flat) breads from the Roman period, which appear to have been very fine and rather free of impurities (such as husk fragments). This suggests the use of ingredients that are well cleaned before milling, as well as the use of free-threshing cereals, initially lowering the proportion of inedible elements likely to be found in the flours. These findings differ from the Metal Age specimens previously studied in Europe, which appear to contain a higher frequency of bran and glume remains. The major shift from hulled towards free-threshing cereals was motivated more by technical constraints weighing on the product intended for sale, than by new dietary habits: free-threshing wheat species could be directly processed. The demand for “ready-to-use” grains has sometimes been coupled with a demand for semi-processed ingredients: in Northern Gaul, we know of certain sites from the late La Tène period documenting milling activities largely exceeding the needs of their occupants, probably partly oriented towards the supply of ground or crushed products. It is likely crucial to include the development of the bakery in this new organization of food trade networks, wherein establishments respond to urban consumers’ needs for basic food products by ensuring the entire chaîne opératoire from grinding grain to selling bread.